(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate hemostatic markers, D. Dimers, PT and APTT in ischaemic stroke patients. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Medical Department of Mardan Medical Complex (Medical Teaching Institute) and Pathology Department of Bacha Khan Medical College, Mardan, from November, 2018 to July, 2019. Materials and Methods: Hundred patients of stroke and fifty healthy individuals were included in this study. All patients and healthy individuals were subjected to hemostatic markers i.e. D. Dimers, PT and APTT. Results: In this study total of 65 patients with stroke showed elevated D. Dimers levels. Eighteen out of 100 i.e. 18% had D. Dimers level in the range of 199-500 ng/ml. Fifteen patients had D. Dimers in the range of 501-1000 ng/ml and 32 out of 100 i.e 32% of the stroke patients showed D. Dimers levels In the range of 1001-2000 ng/ml. Thirty five patients had D. dimers in the normal range. Activated partial prothrombin time (APTT) in 8 patients was found to be shortened. Mean APTT was 33 +.562 seconds. Similarly prothrombin time (PT) in 6 patients was found to be shortened than normal. Mean PT value was 11 + .265 seconds. This study showed that D. Dimers were significantly elevated and PT and APTT were significantly shortened in stroke patients. P value for D. Dimer was P<.00265 and for PT and APTT, P value was < .00326. Conclusion: This study concluded that stroke patients with infarction are associated with significant hemostatic abnormalities which reflect changes in hemostasis and thrombosis. Findings of elevated D. Dimers and shortened PT and APTT in patients with infarction will reduce morbidity and mortality in such patients if properly identified and managed in time.